2021
DOI: 10.1017/s0031182021000330
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Neotropical anuran parasites: a morphological, life cycle and phylogenetic study of Catadiscus marinholutzi (Trematoda: Diplodiscidae)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our reconstruction based on the conservative 28S gene did not support the monophyly of the family Cladorchiidae (sensu Alves et al, 2020), although it was previously suggested (nonetheless, only on the basis of weak support). Even though Opisthodiscus and Megalodiscus share similar morphological traits (e.g., 2 testes, and an oesophagus that is shorter than the pharynx, Sey, 1991), recent phylogenetic analyses based on molecular data (Alves et al, 2020;Queiroz et al, 2021;and this study) suggest that these 2 genera are in paraphyly, and while the position of Opisthodiscus is nested within Diplodiscidae (i.e., a sister position to species of the genus Diplodiscus), Megalodiscus is positioned within Cladorchiidae. Thus, we can only assume that convergent adaptation to amphibian hosts evolved among paramphistomoids in different geographical regions; however, to fully resolve the classification of cladorchiids, more comprehensive morphological evaluation is required.…”
Section: (Ay222212)mentioning
confidence: 52%
See 3 more Smart Citations
“…Our reconstruction based on the conservative 28S gene did not support the monophyly of the family Cladorchiidae (sensu Alves et al, 2020), although it was previously suggested (nonetheless, only on the basis of weak support). Even though Opisthodiscus and Megalodiscus share similar morphological traits (e.g., 2 testes, and an oesophagus that is shorter than the pharynx, Sey, 1991), recent phylogenetic analyses based on molecular data (Alves et al, 2020;Queiroz et al, 2021;and this study) suggest that these 2 genera are in paraphyly, and while the position of Opisthodiscus is nested within Diplodiscidae (i.e., a sister position to species of the genus Diplodiscus), Megalodiscus is positioned within Cladorchiidae. Thus, we can only assume that convergent adaptation to amphibian hosts evolved among paramphistomoids in different geographical regions; however, to fully resolve the classification of cladorchiids, more comprehensive morphological evaluation is required.…”
Section: (Ay222212)mentioning
confidence: 52%
“…Although, the monophyly of Diplodiscidae was not fully supported by Queiroz et al . ( 2021 ), the current addition of Opisthodiscus into phylogeny helps to shed more light on the relationships within this family. Moreover, with further addition of (still missing) molecular data from other genera from the family Diplodiscidae (i.e., Progonimodiscus Vercammen-Grandjean, 1960 (in frogs from Africa), Dermatemytrema Price, 1937 (in turtles from North America), Pseudodiplodiscus Manter, 1962 (in fish from South America) and Australodiscus Sey, 1983 (in frogs from Oceania – Australia) (Sey, 1991 ; Jones, 2005 )) might help to finally resolve relationships of the diplodiscids to the cladorchiids, and further elucidate the historical dispersion routes and diversification within diplodiscids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that molecular analysis is an important tool for the identification and phylogenetic analyses of trematodes (Gomes et al, 2013;Müller et al, 2021;Queiroz et al, 2021;Franceschini et al, 2021). Here, we provide the morphological and the first molecular assessment of G. parvicava from L. labyrinthicus in Brazil using the mitochondrial gene cytochrome c oxidase I (COI) and the large subunit of the 28S ribosomal gene.…”
Section: Phylogenetic Position Of Gorgoderina Parvicavamentioning
confidence: 99%